2014
DOI: 10.1073/pnas.1415403111
|View full text |Cite
|
Sign up to set email alerts
|

Wireless gas detection with a smartphone via rf communication

Abstract: Chemical sensing is of critical importance to human health, safety, and security, yet it is not broadly implemented because existing sensors often require trained personnel, expensive and bulky equipment, and have large power requirements. This study reports the development of a smartphone-based sensing strategy that employs chemiresponsive nanomaterials integrated into the circuitry of commercial near-field communication tags to achieve non-line-of-sight, portable, and inexpensive detection and discrimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 20 publications
1
107
0
Order By: Relevance
“…Recently, mechanical abrasion of compressed either single or multi-walled CNTs directly onto the surface of the paper was suggested as an alternative approach to develop chemiresistive sensors for gas detection. [31][32][33][34][35] These sensing devices exhibited sufficient conductivity (10-30 kΩ) and showed similar/improved sensing characteristics to their counterparts prepared using solventdispersion techniques. More recently, pencil drawn electrodes (PDEs) prepared via mechanical abrasion of graphite on solid substrate have been developed and used as voltammetric sensors for the detection of metal ions.…”
Section: -15mentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, mechanical abrasion of compressed either single or multi-walled CNTs directly onto the surface of the paper was suggested as an alternative approach to develop chemiresistive sensors for gas detection. [31][32][33][34][35] These sensing devices exhibited sufficient conductivity (10-30 kΩ) and showed similar/improved sensing characteristics to their counterparts prepared using solventdispersion techniques. More recently, pencil drawn electrodes (PDEs) prepared via mechanical abrasion of graphite on solid substrate have been developed and used as voltammetric sensors for the detection of metal ions.…”
Section: -15mentioning
confidence: 92%
“…The growth of fields like Big Data heavily relies on the ability to collect large amounts of data, and it has been argued that the next big leap in communication will happen by integrating chemical sensors with mobile communication devices. 35,51,52 Clearly, to enable such advances in chemistry, it would be important to involve members of public in collection of chemical data. This could be achieved with sensors that are so simple and cheap that citizens can prepare and use them at home using simple household items.…”
Section: -15mentioning
confidence: 99%
“…Swelling mechanisms have been posited previously for both polymer-and CNT-based sensors. 2,3,23,24,26,27 We used Raman spectroscopy to examine the changes in the sensing material caused by analytes and found that while relative effects observed in this experiment did not clearly correlate with the magnitude of different responses, both ionic and neutral porphyrin-SWCNT composites exhibited changes in the relative intensities of the radial breathing mode (RBM) absorptions upon exposure to analytes, suggesting that analyte vapors induced changes in CNT-CNT interactions (see Supporting Information figures S9 and S10). 28,29 We observe inverted behavior for the ionic metalloporphyrin composite upon exposure to analyte as compared to the neutral case, a relative increase in the peak at 265 cm -1 rather than a decrease.…”
Section: Supporting Informationmentioning
confidence: 99%
“…The strong responses are dosimetric and could find utility in single-use wireless tags. [19] Detection of BAs in meat samples requires a strategy for distinguishing them from the complex matrix. To assess their selectivity toward amines, we measured responses of [Co(tpp)]ClO4-SWCNT devices to volatile compounds representing a wide range of functional groups ( Figure 5).…”
mentioning
confidence: 99%